La libertad y el orden público en el derecho constitucional francés De vuelta a la decisión del Consejo Constitucional valida la ley que prohíbe la cobertura completa del rostro (2016)
The Law of October 11, 2010 stipulates that “no person shall, in the public space,wear clothing intended to conceal their face”. This statutory provision was the subjectof judicial review by the Constitutional Council. Such authority, in its decisionof October 7, 2010, issued an unprecedented interpretation in the context of therelationship between the notions of liberty and public order, on the basis of Article5 of the Universal Declaration of Human Rights and of the Citizen of 1789.The aforementioned constitutional jurisprudence is important because by limitingfreedom of expression of religious views, even in public space, the French conceptof secularism is reinforced